Effectiveness Test of 96% Ethanol Extract of Black Cumin Seeds (Nigella sativa Linn., Al-Habbah As-Sauda') on Wound Healing and Leukocyte Levels in White Rats (Rattus norvegicus) - Azafanisa Agilta Velovexia; Nasrudin Andi Mappaware; Andi Dhedie Prasatia Sam; Ida Royani; Nur Fadhillah Khalid (Medisains)
Background: Wounds are skin damage that affects the body's protective functions and requires a complex healing process. The utilization of medicinal plants, such as black cumin (Nigella sativa Linn.), has been widely recognized for its antiseptic, anti-inflammatory, and immunomodulatory properties. The active ingredients of black cumin, such as thymoquinone, are known to support wound healing by increasing fibroblast proliferation, collagen synthesis, and reducing infection and inflammation. This study aims to test the effectiveness of 96% ethanol extract of black cumin seeds on incision wound healing and leukocyte levels in white rats (Rattus norvegicus).